Magnetic Signatures on River Sediments and Agricultural Soils as Proxy Indicators of Anthropogenic-derived Pollution (Case Study: Cikijing River, Rancaekek, West Java) - Widya Utami; Siti Zulaikah; Dini Fitriani; Kartika Hajar Kirana; Eleonora Agustine (Jurnal Penelitian Pendidikan IPA, 2021)
A number of activities occur around the Cikijing River in Rancaekek area, West Java, such as industrial and domestic activities. The various activities could decrease the quality of the river and surrounding environment due to anthropogenic pollutants that might be produced. Since the Cikijing River is also used as the source of irrigation, paddy fields around the river could be also be affected. The presence of pollutants in river sediments and agricultural soils over a long period could change their magnetic properties. Magnetic susceptibility of Cikijing River sediments and soils of the paddy fields in the surrounding have been examined considering that magnetic properties could represent environmental conditions. The results show that river sediments have magnetic susceptibility (cLF) in range of 356.2-456.3 (×10-8) m3kg-1, whereas soils samples have cLF varying from 94.1 to 347.1 (×10-8) m3kg-1, suggesting domination of ferrimagnetic minerals. The cFD (%) is <4% indicating the anthropogenic origin of magnetic minerals.  Electron microscopy images show the imperfect octahedral and spherules shapes of magnetic grains that supports magnetic susceptibility analysis about the source of magnetic minerals. Elemental composition analysis reveals Fe and O’s content as main elements, including minor elements of Ca, Mg, Al. Si, Ti and Cr